State of art about the elderly care models on the primary health attention (Research, Society and Development, 2020)
This manuscript presents reflections on health care for the elderly population health in interface to the model cares existent with the primary health attention. The study has the objective reflect about the model of cares directed to the elderly population on primary health attention. The methodological plan treat about a theoretical-reflective essay initially exploratory, oriented by scientific products with qualitative stamp. The findings wore organised by two schematic overview and the distribution of the scientific materials consulted wore organized to be in accordance with the following information: author, year, document title, representation of the consulted material and the subject approached. The discussions wore underway for reflective productions that play two theoretical complementary nucleus. The first one is about the theoretical elements about the Brazilian “Sistema Único de Saúde” in resonance whit the health care models together for the primary health attention and the second one writes about the political elements directed to the elderly health care. It was concluded that the Brazilian health system has been trough for significative changes and was fundamental to the consolidation of the elderly rights consolidation. As regards to the model of biophysical care practice